2023
DOI: 10.1051/0004-6361/202347421
|View full text |Cite
|
Sign up to set email alerts
|

Smooth kinematic and metallicity gradients reveal that the Milky Way’s nuclear star cluster and disc might be part of the same structure

F. Nogueras-Lara,
A. Feldmeier-Krause,
R. Schödel
et al.

Abstract: Context. The innermost regions of most galaxies are characterised by the presence of extremely dense nuclear star clusters. Nevertheless, these clusters are not the only stellar component present in galactic nuclei, where larger stellar structures known as nuclear stellar discs, have also been found. Understanding the relation between nuclear star clusters and nuclear stellar discs is challenging due to the large distance towards other galaxies which limits their analysis to integrated light. The Milky Way’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Such an extension is clearly necessary because a large number of stars with metallicities higher than solar is observed in densely populated regions of the Galaxy, such as in the bulge or in young star clusters within the Galactic center, especially in its main stellar components, i.e., the nuclear star cluster and the nuclear stellar disk. Thorsbro et al (2020), Feldmeier-Krause (2022), and Nogueras-Lara et al (2023), for example, by analyzing quite a large number of giants in the Galactic center, have shown that the metallicities of these stars reaches up to 10 times the solar metallicity. Therefore, the use of stellar yields from SSM sources is essential to study the formation and the chemical evolution of these regions (Cinquegrana & Karakas 2022;Prantzos et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Such an extension is clearly necessary because a large number of stars with metallicities higher than solar is observed in densely populated regions of the Galaxy, such as in the bulge or in young star clusters within the Galactic center, especially in its main stellar components, i.e., the nuclear star cluster and the nuclear stellar disk. Thorsbro et al (2020), Feldmeier-Krause (2022), and Nogueras-Lara et al (2023), for example, by analyzing quite a large number of giants in the Galactic center, have shown that the metallicities of these stars reaches up to 10 times the solar metallicity. Therefore, the use of stellar yields from SSM sources is essential to study the formation and the chemical evolution of these regions (Cinquegrana & Karakas 2022;Prantzos et al 2023).…”
Section: Introductionmentioning
confidence: 99%